1998
DOI: 10.1159/000022442
|View full text |Cite
|
Sign up to set email alerts
|

Relation between Carotid Intima-Media Thickness, Platelet Surface Activation and Endothelial Cell Markers

Abstract: Background: The role of platelet activation and endothelial cell damage in the pathogenesis of atherosclerosis was investigated. Methods: Flow-cytometric detection of platelet activity was accomplished by measuring the surface expression of activated platelet glycoprotein IIb/IIIa (activated CD41) and the lysosomal integral membrane protein (CD63). Levels of thrombomodulin (TM) and von Willebrand factor (vWF) were estimated by the ELISA technique as markers of endothelial cell damage. These procedures were per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…One study showed that habitual snoring is associated with carotid atherosclerosis, 10 which is associated with systemic inflammation 11 as well as endothelial cell damage. 23 The strengths of our study include that the data were derived from a general population, LTL measurements were taken of a large sample size, and both subjective and objective snoring assessments were used. However, our study also has some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…One study showed that habitual snoring is associated with carotid atherosclerosis, 10 which is associated with systemic inflammation 11 as well as endothelial cell damage. 23 The strengths of our study include that the data were derived from a general population, LTL measurements were taken of a large sample size, and both subjective and objective snoring assessments were used. However, our study also has some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…However, this platelet hyperactivation had already been in existence during the process of carotid atherosclerosis before any acute vascular events [9, 10]and still remained in patients with chronic atherosclerotic ischemic stroke [11, 12]. Therefore, it is possible that the increased expression of CD63 and P-selectin on platelets may simply reflect the ongoing inflammatory processes of atherogenesis of the carotid or vertebrobasilary arteries rather than the effect of acute vascular events.…”
Section: Introductionmentioning
confidence: 99%
“…However, in symptomatic plaque, increased expression of both CD163 and heme oxygenase-1 has been found, which suggests that these may have been upregulated in response to plaque hemorrhages [34]. CD63 was increased in a rabbit model of atherosclerosis as well as plaque isolated from human vessels [35]. The role of CSF2RB is largely unstudied in atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%